2020
DOI: 10.1152/ajplung.00309.2019
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A3 confers protection against acute lung injury inPseudomonas aeruginosa-infected mice

Abstract: Pseudomonas aeruginosa is a gram-negative bacterium associated with serious illnesses, including ventilator-associated pneumonia and various sepsis syndromes in humans. Understanding the host immune mechanisms against P. aeruginosa is, therefore, of clinical importance. The present study identified serum amyloid A3 (SAA3) as being highly inducible in mouse bronchial epithelium following P. aeruginosa infection. Genetic deletion of Saa3 rendered mice more susceptible to P. aeruginosa infection with decreased ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Through the use of animal models, several studies have demonstrated upregulated expression of SAA upon bacterial infection. 30,31 Whether or not SAA expression occurs in vivo directly in response to TLR ligands or via upregulated inflammatory cytokines is unknown. Nevertheless, in vitro studies have demonstrated the expression of SAA by human hepatocytes in response to the bacterial product LPS.…”
Section: Leucocyte Attractionmentioning
confidence: 99%
“…Through the use of animal models, several studies have demonstrated upregulated expression of SAA upon bacterial infection. 30,31 Whether or not SAA expression occurs in vivo directly in response to TLR ligands or via upregulated inflammatory cytokines is unknown. Nevertheless, in vitro studies have demonstrated the expression of SAA by human hepatocytes in response to the bacterial product LPS.…”
Section: Leucocyte Attractionmentioning
confidence: 99%
“…For instance, mice lacking the gene encoding serum amyloid P (Apcs) are susceptible to pneumonia, providing an important example whereby a specific factor contributes to lung immunity (83). Similar results have been reported for other APPspecific knockout mice (86,87), but this strategy neither accounts for baseline APP concentrations nor does it specify the importance of hepatocytes as the origin of gene expression. In all likelihood, the benefits of STAT3-driven hepatocyte activity observed in our prior and current studies are due to integrated contributions from multiple factors that alter lung immunity in a complex and coordinated fashion.…”
Section: Figurementioning
confidence: 77%
“…PA and MHV infections were performed as previously described. 26 , 27 For the IL-6 treatment, mice were treated intranasally with mouse recombinant IL-6 protein (R&D, Minneapolis, MN) at a dosage of 25ug per mouse, diluted with PBS with 0.1% BSA to 50 µL, intranasal inoculated on day 4, 5, 6, 7 post infection. 28 BALF samples and lung tissues were harvested at day 8 post-infection.…”
Section: Methodsmentioning
confidence: 99%